2020
DOI: 10.1097/cmr.0000000000000662
|View full text |Cite
|
Sign up to set email alerts
|

BRAF and MEK inhibitors rechallenge as effective treatment for patients with metastatic melanoma

Abstract: Despite considerable progress made in the treatment of patients with advanced melanoma, the majority of the patients treated with BRAF and mitogen-activated protein inhibitors (BRAFi and MEKi) experience a disease progression due to acquired resistance. Currently, ongoing studies explore the possibility to overcome or reverse this process. Our multicenter retrospective analysis included 51 patients with metastatic BRAF-mutated melanoma who had previously progressed on BRAFi/MEKi than had progressed on immunoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…The correlation between duration of treatment break and clinical outcome is unclear. Valpione et al reported that the duration of treatment break (6.7-8.8 months) seems to be correlated with clinical outcome (14) while retrospective analyses and one prospective clinical trial did not confirm this finding (15)(16)(17). In our patients, the duration of the interval between treatments was more than 6 months for all cases but we observed mixed outcomes: two patients had long-term control of the disease (patient 1 and 2) and one patient (patient 3) had only a shortlived stabilization of symptoms (1 month) rapidly followed by a multi-site progression of disease.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The correlation between duration of treatment break and clinical outcome is unclear. Valpione et al reported that the duration of treatment break (6.7-8.8 months) seems to be correlated with clinical outcome (14) while retrospective analyses and one prospective clinical trial did not confirm this finding (15)(16)(17). In our patients, the duration of the interval between treatments was more than 6 months for all cases but we observed mixed outcomes: two patients had long-term control of the disease (patient 1 and 2) and one patient (patient 3) had only a shortlived stabilization of symptoms (1 month) rapidly followed by a multi-site progression of disease.…”
Section: Discussionmentioning
confidence: 98%
“…Another recent multicenter retrospective analysis investigated the retreatment with BRAFi and MEKi combination in 51 patients with metastatic BRAF-mutated melanoma, previously progressed after receiving kinase inhibitors (BRAFi and MEKi or BRAFi alone) and immunotherapy (anti-PD-1 or anti-CTLA-4) (16). The median PFS and OS for the rechallenge combination treatment was 5.9 and 9.3 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the RR exceeds that obtainable with immunotherapy alone, suggesting the possible overcoming of the previously acquired resistance to BRAFi. More recently, a multicenter retrospective study [83] evaluated 51 patients with progressive disease after first line of treatment with BRAFi/MEKi and second line immunotherapy with anti PD1/PDL1 or anti CTLA4. Patients were rechallenged with BRAFi/MEKi, with an overall response rate of 27%.…”
Section: Rechallenge Retreatment and Intermittent Treatmentmentioning
confidence: 99%